Biomimetic Color Changing Anisotropic Soft Actuators with Integrated Metal Nanowire Percolation Network Transparent Heaters for Soft Robotics - Kim, Hyeonseok; Lee, Habeom; Ha, Inho; Jung, Jinwook; Won, Phillip; Cho, Hyunmin; Yeo, Junyeob; Hong, Sukjoon; Han, Seungyong; Kwon, Jinhyeong; Cho, Kyu Jin; Ko, Seung Hwan (Advanced Functional Materials, 2018)
To add more functionalities and overcome the limitation in conventional soft robots, highly anisotropic soft actuators with color shifting function during actuation is demonstrated for the first time. The electrothermally operating soft actuators with installed transparent metal nanowire percolation network heater allow easy programming of their actuation direction and instantaneous visualization of temperature changes through color change. Due to the unique direction dependent coefficient of thermal expansion mismatch, the suggested actuator demonstrates a highly anisotropic and reversible behavior with very large bending curvature (2.5 cm−1) at considerably low temperature (≈40 °C) compared to the previously reported electrothermal soft actuators. The mild operating heat condition required for the maximum curvature enables the superior long-term stability during more than 10 000 operating cycles. Also, the optical transparency of the polymer bilayer and metal nanowire percolation network heater allow the incorporation of the thermochromic pigments to fabricate color-shifting actuators. As a proof-of-concept, various color-shifting biomimetic soft robots such as color-shifting blooming flower, fluttering butterfly, and color-shifting twining tendril are demonstrated. The developed color-shifting anisotropic soft actuator is expected to open new application fields and functionalities overcoming the limitation of current soft robots.
Keywords: Anisotropic thermal expansion; Color changing; Low temperatures; Percolation networks; Soft robot; Ag nanowire percolation networks; anisotropic actuators; anisotropic thermal expansion; color-changing actuators; low-temperature actuators; soft robots